Mammary benign neoplasm diagnosed by fine needle aspiration biopsy in a guinea pig (Cavia porcellus) - Grandi, Fabrizio; Monteiro, Lidianne Nardicci; Marietto-Gonçalves, Guilherme Augusto; Rocha, Noeme Sousa [UNESP] (My University, 2011)
Cytology is a well established research technique in human and veterinary medicine, but it is rarely used in small rodents. Spontaneous tumors are relatively uncommon in guinea pigs and those described in literature include a variety of organs like skin and subcutis, respiratory and reproductive tract, endocrine and hematopoietic system, and mammary gland. The objective of this article was to describe the use of the fine needle aspiration biopsy technique (FNAB) on evaluation of a mammary neoplasm in a guinea pig and describe the main cytological findings for the first time in literature.
Keywords: Cytology; Guinea pig; Mammary gland; Neoplasia; Pathology; Tumor; Cavia; Cavia porcellus; Rodentia